Navigating (homo)nationalism and heteronormativity; how Turkish-Dutch and Moroccan-Dutch gay/bi men negotiate belonging in Amsterdam. Issue 141 (May 2023) - van Gent, Wouter; Brugman, Gerald; De Craene, Valerie
Abstract: Current-day nationalist ideologies imagine immigrant communities, and particularly Muslims, as traditionalist and backward subjects. They often propagate the importance of sexual and gender equality as a way to 'other' non-white minorities ('homonationalism'). This study seeks to understand how (homo)nationalism affect senses of self and belonging for those who do not fit discursive binaries: non-heterosexual minorities. As such, we seek to contribute to geographical understandings of everyday experiences of sexual and racial politics in Western European cities. We interviewed seventeen Turkish-Dutch and Moroccan-Dutch non-heterosexual cismen in the Amsterdam region, focusing on their spatial perceptions, everyday encounters, and negotiations of subjectivities in urban space. While almost all of these men are subjected by (homo)nationalism, they negotiate their social and spatial trajectories in diverse ways. These findings show how nationalist politics affect everyday lives at the urban scale, while also highlighting how those denied belonging navigate multiple forms of exclusion.